Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.2 - Solving Quadratic Equations by Completing the Square - Exercise Set - Page 775: 2


$p=1$ and $p=-12$

Work Step by Step

$p^{2}+11p-12=0$ Use the quadratic formula to solve this equation. The formula is $p=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$ For this equation, $a=1$, $b=11$ and $c=-12$ Substitute: $p=\dfrac{-11\pm\sqrt{11^{2}-4(1)(-12)}}{2(1)}=\dfrac{-11\pm\sqrt{121+48}}{2}=...$ $...=\dfrac{-11\pm\sqrt{169}}{2}=\dfrac{-11\pm13}{2}$ Our two solutions are: $p=\dfrac{-11+13}{2}=1$ $p=\dfrac{-11-13}{2}=-12$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.